Mental Status Examination - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The child neurologists' approach to the mental status examination of children with learning problems was examined by questionnaires randomly submitted to 163 attendees at the 16th Annual Child Neurology Society Meeting in 1987 and the results are reported from the Division of Neurology, Department of Pediatrics, Newington Children's Hospital and Biostatistics Research Center, Farmington, Connecticut.